Determining priority criteria for industry 4.0 maturity models in small and medium enterprises in Indonesia - Nabilah, Nabilah; Hisjam, Muh; Sutopo, Wahyudi (Operations Excellence: Journal of Applied Industrial Engineering, 2023)
For manufacturing companies, especially Small and Medium Enterprises (SMEs), currently measuring the level of the Maturity Model (MM) is not an easy thing to do, because there are still many obstacles, including not knowing what factors are priorities in developing the MM. This research aims to identify the criteria that influence the measurement of maturity model based on survey results in small and medium enterprises. Using the Fuzzy DEMATEL method to find the priority and causality of each criterion attribute. The research results show that the Advanced IT criteria is the first priority to be considered to have the most influence on measuring the industry 4.0 maturity model.